Pengaruh Kompleksitas Tugas, Independensi Dan Pengetahuan Auditor Terhadap Audit Judgment Dikantor BPKP Sumatra Barat - Annisa Annisa; Bima Rahma Wiguna (Pusat Riset dan Inovasi Nasional, 2023)
Audit judgment is the auditor's personal judgment or opinion in responding to information that influences decisions that affect audit evidence documents and the auditor's opinion on the financial statements of an entity. As a cognitive process, audit judgment is a decision-making behavior. Accountants are often faced with decisions that are not in accordance with generally accepted ethical standards or accounting principles. This research aims to find out and analyze how much influence task complexity (X1), independence (X2) and auditor knowledge (X3) have on audit judgment (Y) at the BPKP office of West Sumatra Province. analysis technique used multiple linear regression. based on research (X1), (X2) has no effect while (X3) has an effect on audit judgment.